Faktor-faktor yang mempengaruhi minat investasi kalangan milenial: Sebuah systematic literature review - Sari, Dela Puspita; Shobri, Muhammad; Zelpani (CV.Karoteh Utama, 2024)
The persistent rise in inflation has encouraged the millennial generation to seek alternative ways to preserve their wealth, with investment emerging as a popular option. This study aims to analyze the factors influencing investment interest among millennials through a systematic literature review (SLR) approach. Articles were collected using the Publish or Perish 8 application from the Google Scholar database, yielding 321 articles published between 2019 and 2024. After applying inclusion criteria, 30 relevant articles were selected for in-depth review. The findings show that investment interest among millennials, particularly those aged 30 and below, has continued to increase. Most of the reviewed studies applied quantitative methods. Seven key factors were identified as influencing millennial investment interest: return and capital gain, investment literacy, investment motivation, minimum capital, capital market training, risk perception, and the influence of social media influencers. These findings highlight the importance of financial literacy and digital technology in enhancing young investors' awareness and participation. This study is expected to serve as a reference for developing investment education programs tailored to the needs of the millennial generation.